Inherent safety index module (ISIM) to assess inherent safety level during preliminary design stage - A.M., Shariff; C.T., Leong (2008)

(untitled)
One of the acceptable methods to quantify the level of inherent safety is based on the inherent safety index. This paper reviews presently available techniques for quantification of inherent safety level in a design and addresses the shortcoming of current techniques by proposing direct integration of process design simulator with inherent safety index. This integrated index is known as inherent safety index module (ISIM) and it is one of the modules developed in a newly proposed framework to determine inherent safety level in the preliminary design stage. This framework is an enhancement of the framework developed earlier by Mohd Shariff et al. [Mohd Shariff, A., Rusli, R., Chan, T.L., Radhakrishnan, V.R. and Buang, A., 2006, Inherent safety tool for explosion consequences study, J Loss Prev Process Ind, 19: 409-418]. This new framework allows process information from process design simulator to be extracted and analyzed for the determination of inherent safety level (ISL), consequences and probability of unwanted incidences. The availability of such information at earlier stage of design will help process designers to obtain ISL that will assist them in producing safer designs by the application of inherent safety principles in a more efficient and cost effective manner. This paper also discusses the overall concept of the proposed framework to produce an inherent safety tool. A case study is provided to illustrate the benefit of having inherent safety index known to process designers during preliminary design stage. With the right information, modification to process conditions can be carried out and this is likely to produce a safer process plant. Â© 2007 The Institution of Chemical Engineers.